Hubungan Pola Asuh Orang Tua dengan Perilaku Merokok pada Remaja Laki-Laki - Yeni Susanti; Burhan Muslim; Edo Gusdiansyah (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2026)
Smoking behavior is bad behavior, especially for teenagers who are still in junior high school. In a survey obtained at SMPN 12, Nanggalo District, Padang City, of the 10 students interviewed, there were 9 students who had smoked because it affected the parenting style given by their parents. The aim of this research is to determine the relationship between parenting patterns and smoking behavior in adolescent boys at SMPN 12, Nanggalo District, Padang City in 2023.This research was conducted at SMPN 12, Nanggalo District, Padang City in December 2022-August 2023. This of research is quantitative, the design used is descriptive analytic with a cross-sectional approach. The population 249 students and the sample 71 respondents. Data collection techniques using random sampling techniques. Data collection was carried out for 2 days on 19-20 June 2023 by filling in a questionnaire. Data were analyzed univariately and bivariately using the Chi-quare test. The results showed that less than half (46.5%) were heavy smokers, less than half (42.3%) had permissive parenting styles. There is a relationship between parenting patterns and smoking behavior among maleteenagers at SMPN 12, Nanggalo District, Padang City in 2023 with p-value=0.001 (p,0.05). The conclusion of this study is that parenting style is very influential in shaping adolescentbehavior.